(untitled) (International Journal of Physiotherapy, 2015)
Background: Children adopting different styles of sitting in class rooms may have an influence over the hamstring length which indirectly produces an effect on posture, gait and musculoskeletal problems. Hence, physiotherapists play an important role in preventing the problems that are to be developed due to the sitting posture adopted at school. Hence, it is important for all the health professionals to understand and know about the effect of different sitting styles of children in school over the children health.The purpose of this study was to determine the influence of two sitting postures (crossed leg sitting and bench sitting) on hamstring flexibility in school going children. Aim of the Study to observe the influence of bench sitting and crossed-leg sitting on hamstring flexibility in school going children. Methods: 200 school children (105 boys and 95 girls) from private schools (those who are bench sitting) and 200 school children (109 boys and 91 girls) from government schools (those who are crossed leg sitting) aged 6-10 years were included in this study. Active Knee Extension (AKE) test with the aid of a simple and economically cheap stabilizing apparatus was used to determine hamstring flexibility. Measurements were taken for both right and left knee. Results: The mean Active Knee Extension (AKE) score for bench sitting children was 132.4 and for crossed leg sitting children was 130.1. The difference observed in knee extension range of motion between the groups was statistically significant (p<0.05). Conclusion: Hamstring flexibility was greater in bench sitting children as compared to crossed leg sitting children.